Thirst for Knowledge: Exploring Dubai’s Water Quality through a Public Health Lens - Foteih, Yassen Al; Karkain , Rashed; Abdulla, Salimbabu; Kharaba, Zelal (International Journal of Membrane Science and Technology, 2023)
The current study aimed to evaluate the biochemical quality of both bottled water and tap water in the Emirate of Dubai. A total of sixty samples were collected (6 Brand x 10 samples each), while an additional 10 samples were taken from the tap water source. The analysis results were then compared to international standards established by IBWA, FDA, USEPA, WHO, and Abu Dhabi’s specific standards. The objective was to identify any potential risks or hazards to public health arising from chemical or biological contaminants in the water. The study assessed various parameters, including total alkalinity, total hardness, and heavy metals, all of which were found to fall within international limits. Microbial content was also analyzed and compared to various standards. The results of this analysis demonstrated that the water’s composition met the international norms for safe drinking water. To investigate the impact of different sodium concentrations on blood tonicity, a qualitative microscopic assessment was employed. The results revealed that sodium concentrations exceeding 3mg/L rendered the cells hypertonic. Any further increase in sodium concentration beyond this level directly correlated with increased cell hypertonicity. However, further research is required to delve into other critical aspects of water consumption in the UAE, such as public attitudes toward water and the influence of water pricing on residents’ purchasing choices. Public awareness campaigns are essential to rectify misconceptions about both tap water quantity and bottled water quality.